2020
DOI: 10.38212/2224-6614.2447
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopic determination of olive oil adulteration with sunflower and corn oil

Abstract: Determination of authenticity of extra virgin olive oils has become very important in recent years due to the increasing public concerns about possible adulterations with relatively cheap vegetable oils such as sunflower oil. This study was focused on the application of near infrared (NIR) spectroscopy in conjunction with multivariate calibration to identify the adulteration of olive oils. NIR transmittance measurements were made on pure olive oil and olive oil adulterated with varying concentrations (4-96%, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Another study on olive oil counterfeiting, applying FT-NIR in the 1000–2500 nm range, revealed that the standard error of predictions ranged between 2.49 and 2.88% V / V for the olive-sunflower oil binary mixture, and 1.42–6.38% V / V for the ternary mixtures of olive–sunflower–corn oil. The R 2 values of models estimating olive oil content were typically more than 0.99 [ 117 ].…”
Section: Near Infrared (Nir) Spectroscopy: Historical Background Amentioning
confidence: 99%
“…Another study on olive oil counterfeiting, applying FT-NIR in the 1000–2500 nm range, revealed that the standard error of predictions ranged between 2.49 and 2.88% V / V for the olive-sunflower oil binary mixture, and 1.42–6.38% V / V for the ternary mixtures of olive–sunflower–corn oil. The R 2 values of models estimating olive oil content were typically more than 0.99 [ 117 ].…”
Section: Near Infrared (Nir) Spectroscopy: Historical Background Amentioning
confidence: 99%
“…They can serve to differentiate samples that rely on spectral information. This refers to the construction of the discriminant model [26,27]. As spectra differ, it is also possible to establish the relation between spectral data and certain properties such as IT, which results in the construction of the reference model [28].…”
Section: Fat Characterization By Ft-irmentioning
confidence: 99%
“…For example, around 1,500,000 children die due to diarrhea every year [13]. Heavy metals are highly toxic and also create a lot of environmental concerns [2,[14][15][16]. To address these issues, there is an urgent need for effective systems for frequently monitoring water quality parameters.…”
Section: Introductionmentioning
confidence: 99%